2019
DOI: 10.3390/pr7070420
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Fluid Dynamics Approach for the Modeling of Gas Separation in Membrane Modules

Abstract: Natural gas demand has increased rapidly across the globe in the last decade, and it is set to play an important role in meeting future energy requirements. Natural gas is mainly produced from fossil fuel and is a side product of crude oil produced beneath the earth’s crust. Materials hazardous to the environment, like CO2, H2S, and C2H4, are present in raw natural gas. Therefore, purification of the gaseous mixture is required for use in different industrial applications. A comprehensive computational fluid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…i denotes the gas species in air. R i is the reaction rate of species i, which is zero because no chemical reaction is involved in the air dehumidification process [ 15 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…i denotes the gas species in air. R i is the reaction rate of species i, which is zero because no chemical reaction is involved in the air dehumidification process [ 15 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The simulation of membrane separation processes (such as gas–gas, gas–liquid, liquid–solid, etc.) has been carried out by many researchers using the function of computational fluid dynamics (CFD) models [ 11 , 14 , 15 , 16 , 17 ]. However, only a couple of studies focused on the water vapor separation of polymeric-based hollow fiber membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the model are presented in our previous study with unrestricted access [ 16 ]. Though concentration polarization effects for gas permeation are reported negligible by several publications [ 18 , 19 , 20 ] due to the high diffusivity and low permeability of gases, we still need to clarify that the disregard of the phenomena in this primary assessment ensures that we are sufficiently cautious when presenting the lower limit for H 2 O/H 2 selectivity. This is because, in the latter case, we overestimate the performance of the MR-based process during the comparison with the CR-based process.…”
Section: Process Description and Simulationmentioning
confidence: 99%
“…The following assumptions were made in the proposed model: Local permeation and bulk permeate flow are described by a crossflow pattern [ 22 , 23 ]; There is no permeate mixing in the direction of the bulk permeate flow [ 19 , 23 ]; The pressure variation for flow through the permeate spacer channel is characterized by Hagen–Poiseuille equation [ 24 ]; The feed-side pressure drop is negligible [ 15 , 16 , 19 , 20 , 23 , 24 ]; The pressure drop along the central permeate collector tube is neglected (i.e., pressure is considered as atmospheric) [ 25 , 26 ]; The permeability coefficients are independent of concentration, pressure, and temperature [ 15 , 16 , 19 , 20 , 23 , 24 ]; Channel curvature is neglected and the membrane is treated as a flat sheet [ 22 , 26 ]; Operation within the SWM module is isothermal [ 16 , 18 , 19 , 20 , 27 ]. …”
Section: Model Developmentmentioning
confidence: 99%
“…Results demonstrated that the increase in the effective area, membrane temperature, and total feed pressure would increase the recovery of the fast component in the permeate side, while the feed flow rate had an adverse effect. The study of comprehensive computational fluid dynamics (CFD) was also conducted by Qadir and Ahsan [ 19 ] in order to analyze membrane-based gas separation for binary gas mixtures. In the most recent work, Dias et al [ 20 ] presented a simplified approach of a 2D permeation model for SWMs in binary gas separation applications.…”
Section: Introductionmentioning
confidence: 99%